Secure Control for Variable Periodic Switched Positive Systems Under Periodic DoS Attack - LIU Jiao, KONG Xiangna, ZHANG Tiantian (Shanghai Jiaotong Daxue xuebao, 2023)
Periodic denial-of-service (DoS) attack prevents the information exchange of measurement channel and control channel for switched positive systems through the network. Moreover, the coupling of system switching behavior and hybrid behavior due to DoS attack and positive constraint also increase the difficulty in secure control research. The secure control problem of networked switched positive systems under periodic DoS attack is studied and a modeling method based on switching behavior is proposed in this paper. Under variable periodic switching, the multiple linear copositive Lyapunov function is constructed to obtain the positive and asymptotically stable condition for the closed-loop system by limiting the relationship between the switching period and the DoS attack period, and a secure state feedback controller based on the positive system theory is designed, based on which, the constant periodic switching case is also discussed by using the positive system theory. Finally, the validity of the results is verified by a simulation example.